PENGARUH ENVIRONMENTAL DISCLOSURE, KUALITAS AUDITOR INTERNAL, DAN KONTRAK MANAJEMEN TERHADAP KUALITAS LABA (Pada Perusahaan Indeks Kompas 100 yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Eksandy, Arry; Milasari, Ema (COMPETITIVE, 2019)
This study aims to determine the effect of environmental disclosure, the quality of internal auditors, and management contracts on earnings quality. Earnings quality is one indicator of the high and low quality of the company's financial information. Profits that do not show actual financial information about management performance can mislead the users of financial statements. The population of this study was conducted at Kompas 100 Index Company listed on the Indonesia Stock Exchange in the 2013-2016 period. Data is obtained through the website www.idx.co.id and the website of each sample company. This study uses a non-probability sampling method with purposive sampling technique so that the number of samples obtained is 9 companies with a total of 36 observations. This study uses panel data regression analysis techniques with the help of software Eviews 9.0. The results of this study are that environmental disclosure and management contracts partially have no effect on earnings quality, while the quality of internal auditors partially negatively affects earnings quality. Â Keywords: Profit Quality, Environmental Disclosure, Quality of Internal Auditors, and Management Contracts